2017
DOI: 10.1186/s13071-017-2113-9
|View full text |Cite
|
Sign up to set email alerts
|

Mesocarnivores and macroparasites: altitude and land use predict the ticks occurring on red foxes (Vulpes vulpes)

Abstract: BackgroundThe red fox Vulpes vulpes is the most common mesocarnivore in Europe and with a wide geographical distribution and a high density in most terrestrial habitats of the continent. It is fast urbanising species, which can harbor high numbers of different tick species, depending on the region. Here we present the results of a large-scale study, trying to disentangle the intricate relationship between environmental factors and the species composition of ectoparasites in red foxes. The samples were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
0
14
1
Order By: Relevance
“…The observed prevalence of subcutaneous ticks (88.1%) in the present study is higher than in Poland (38%) [20] and Czech Republic/Romania (15.4%) [18]. Moreover, the prevalence of subcutaneous ticks is higher in comparison with external tick prevalence in red foxes from Italy (7.4%) [29] and Romania (53.9%) [30], but coincides to studies from Spain (51.1-84.6%) [31][32][33] and Germany (76.5-82.6%) [7,34]. Additionally, the infestation intensity of subcutaneous ticks (mean = 10.8) in the present study is similar to external ticks from another study examining 1268 foxes in Germany (mean = 11.7) [34].…”
Section: Discussioncontrasting
confidence: 59%
“…The observed prevalence of subcutaneous ticks (88.1%) in the present study is higher than in Poland (38%) [20] and Czech Republic/Romania (15.4%) [18]. Moreover, the prevalence of subcutaneous ticks is higher in comparison with external tick prevalence in red foxes from Italy (7.4%) [29] and Romania (53.9%) [30], but coincides to studies from Spain (51.1-84.6%) [31][32][33] and Germany (76.5-82.6%) [7,34]. Additionally, the infestation intensity of subcutaneous ticks (mean = 10.8) in the present study is similar to external ticks from another study examining 1268 foxes in Germany (mean = 11.7) [34].…”
Section: Discussioncontrasting
confidence: 59%
“…Recently, ticks resembling I. kaiseri were reported in Poland [33]. Although I. kaiseri was previously reported from Romania [34], this was not confirmed by later studies involving or reporting ticks of carnivores [8, 35–37]. Here, the evidence is provided for the occurrence of I. kaiseri in Romania, as well as in three other countries, where it had not been reported yet (Germany, Hungary and Serbia).…”
Section: Discussionmentioning
confidence: 64%
“…However, there is no evidence of its permanent establishment. Moreover, none of the previous studies of ectoparasites of domestic and wild carnivores in Romania reported the presence of H. longipennis (Dumitrache et al ., ; D'Amico et al ., , ; Foley et al ., ; Sándor et al ., ). It should be noted that Hippobosca equina has also been reported in dogs from Albania (Danielova, ) and Poland (Sokół & Gałecki, ).…”
Section: Discussionmentioning
confidence: 97%